6+0.5x=42

Simple and best practice solution for 6+0.5x=42 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6+0.5x=42 equation:


Simplifying
6 + 0.5x = 42

Solving
6 + 0.5x = 42

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 0.5x = 42 + -6

Combine like terms: 6 + -6 = 0
0 + 0.5x = 42 + -6
0.5x = 42 + -6

Combine like terms: 42 + -6 = 36
0.5x = 36

Divide each side by '0.5'.
x = 72

Simplifying
x = 72

See similar equations:

| 3a+8=26 | | 4(q+3)+2q=-12 | | 6a+4b+4a+5a= | | 10x-2-6x=3x+2+x | | 7*0.15+0.15s=5.55 | | 2F-7.9-F+1.5=-3.2-1.7 | | 8m-9n-2n=6n | | -8=2(3-2n) | | 11x+12=5x+60 | | 3(y-3)=2y+9+y | | -5E-32+6E=19 | | -2(4+x)=25 | | 3.29-0.14x=5x-3.135 | | x^3+x^2+36*x-23=0 | | 7x+2y+(-8x)-3y= | | 40+s=61 | | 11=c-2 | | 4(x-1)-(3x+2)=2(x+7) | | 54x^2+40x=0 | | -1.80=4.0x-4.9(x^2) | | 5x-12=6x-16 | | -10-m=6m-10 | | x^3-19683=0 | | 9x-2(x-7)=2(x-2)+1 | | 5p=2p-4qforp | | -1.80=4.9x-4.9(x^2) | | -4=-5+x | | -2m+(-6m)= | | 10x-1=9x+8 | | 8(y+3)=4Y+32 | | 4x+(-3x)= | | -16-5z=51 |

Equations solver categories